2017
DOI: 10.1016/j.jsames.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology and landscape evolution of the strand-plain of the Usumacinta and Grijalva rivers, southern Mexico

Abstract: The strand-plain of the Usumacinta and Grijalva rivers is the largest of the Gulf of Mexico as it is characterized by a sequence of well-preserved beach-dune ridges (n > 100) distributed ~150 km along the shoreline. This prominent coastal landform is part of the delta plain of Tabasco and Campeche. We present geochronogical data of the beach-dune ridges sequence of the Usumacinta and Grijalva rivers. Radiocarbon dating failed in providing consistent ages of the ridges in contrast to optically stimulated lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…Chávez Jiménez (2007) estimated that delta progradation has occurred from 1519 to 2000 CE (431-0 BP), extending the mouth of the Grijalva 8–10 km offshore and 20–25 km along the coast, substantially reconfiguring the deltas and bar systems through these centuries. The historical map-based model agrees with the post-Contact delta geochronology of Muñoz-Salinas et al (2017), with the present-day township of Frontera (considered by some scholars as the approximate location of the important Late Postclassic/Protohistoric site of Pontochán) located on the coastline at the time of Spanish Contact. By contrast, the chronology of Nooren et al (2017) suggests that the final major phase of coastal progradation had finished by the time of Contact (c. 1500 CE; 450 BP).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Chávez Jiménez (2007) estimated that delta progradation has occurred from 1519 to 2000 CE (431-0 BP), extending the mouth of the Grijalva 8–10 km offshore and 20–25 km along the coast, substantially reconfiguring the deltas and bar systems through these centuries. The historical map-based model agrees with the post-Contact delta geochronology of Muñoz-Salinas et al (2017), with the present-day township of Frontera (considered by some scholars as the approximate location of the important Late Postclassic/Protohistoric site of Pontochán) located on the coastline at the time of Spanish Contact. By contrast, the chronology of Nooren et al (2017) suggests that the final major phase of coastal progradation had finished by the time of Contact (c. 1500 CE; 450 BP).…”
Section: Resultssupporting
confidence: 76%
“…We present the transitions ages between the three different phases (Table 2). Muñoz-Salinas et al (2017) showed that the Maya Classic period occurred at the end of Delta phase 1 and beginning of phase 2, c. 1200 BP , whereas Nooren et al (2017) indicated this c. 600-years period happened entirely during phase 2 (Figure 7(b)). The transition between phases implies the switching in the river outlets on the deltas (Figure 7(a)), probably caused by an avulsion, generally associated with extraordinary floods (Jones and Schumm, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The depositional rates between 6 and 1.8 m a -1 in the strand-plain of Nayarit are indicating that progradation rate is slightly lower than those reported for the strand-plain of the Usumacinta and Grijalva rivers that are estimated in 4.7 to 8.8 m a -1 (Muñoz-Salinas et al, 2017). The depositional rates of the Nayarit strand-plains are, however, high in comparison to those rates reported in other strand-plains around the world.…”
Section: Landscape Evolution Of the Strand-plain Of Nayaritmentioning
confidence: 53%
“…The Carrizal River joins the Usumacinta River before discharging into the Gulf of Mexico while the Samaria River discharges directly to the Gulf. However, sediment records show that in the past the Mezcalapa River drained in a more direct route to the Gulf (Muñoz-Salinas et al, 2017) as depicted in Figure 2 with the Seco River paleochannel.…”
Section: Location and Fluvial System Characterizationmentioning
confidence: 99%